Dynamics of dwarf shrubs in Mediterranean high‐mountain ecosystems. (25th August 2022) - De Toma, Andrea; Carboni, Marta; Bazzichetto, Manuele; Malavasi, Marco; Cutini, Maurizio
Abstract: Question: Vegetation around the alpine–treeline ecotone faces changes in both climate and land use (i.e. grazing abandonment). Broad‐scale shrub encroachment is considered an effect of these changes, but it remains unclear how this process is mediated by local‐scale environmental heterogeneity. Our goal is to determine which local‐scale environmental factors shape the spatial distribution and temporal trends of alpine dwarf shrub vegetation dominated by Juniperus communis in Mediterranean mountains. Location: Three sites in the Central Apennine Mountain Range (Italy): Mt. Terminillo, Mt. Duchessa and Mt. Ernici. Methods: Combining a set of environmental variables obtained at a fine scale (25‐m resolution) from multi‐year remote sensing imagery and field‐collected vegetation data, we modelled the occurrence and cover of Juniperus communis ‐dominated dwarf shrubland, as well as its change over time, as a function of local climate, topography and land use, using linear and generalized mixed effects models. Results: Over a period of almost 60 years (1954–2012) shrubland occurrence increased by 12% and shrubland cover by 10% in our study sites. Its current distribution and change over time appear to be strongly shaped by the joint influences of fine‐scale topography, above‐ground biomass, land use and microclimate. Shrublands have been favoured locally in areas with harsher alpine environmental constraints and stronger resource limitations. Conclusions: Our study shows that in the Mediterranean high‐mountain environment J. communis dwarf shrubland acts as a stress‐tolerant pioneer vegetation, occurring in areas that are otherwise sparsely vegetated. Contrary to our expectations, at fine scales, warmer temperatures and the regional decline in grazing did not favour shrub encroachment. Despite increasing overall, J. communis shrubs have little competitive ability to successfully encroach grasslands, and remain restricted to less‐productive areas. Our results confirm that fine‐scale environmental heterogeneity can strongly influence shrub distribution and dynamics, thereby modulating future responses in evolving alpine ecosystems. Abstract : We modelled the distribution of Juniperus communis dwarf shrubland, as well as its change over time, as a function of fine‐scale environmental variables from multi‐year remote sensing and field‐collected data. Our shrubland acts as a stress‐tolerant pioneer vegetation, occurring in areas that are otherwise sparsely vegetated. Despite increasing overall, local warmer temperatures and declines in grazing did not favour shrub encroachment.